MINERALOGY AND NOBLE-GAS SIGNATURES OF THE CARBONATE-RICH LITHOLOGY OF THE TAGISH LAKE CARBONACEOUS CHONDRITE: EVIDENCE FOR AN ACCRETIONARY BRECCIA - Nakamura T.; Noguchi T.; Zolensky M.E.; Tanaka M. (My University, 2003)
The carbonate-rich lithology of the Tagish Lake carbonaceous chondrite was characterized by noble-gas mass spectrometry, synchrotron X-ray diffraction analysis, and transmission and scanning electron microscopy. Noble-gas analysis was performed on two samples and the results showed that primordial noble gases are abundant and solar noble gases are absent in the samples of carbonate-rich lithology. The concentrations of Ne-A2 and -E in both samples are at the maximum level observed for CI and CM chondrites, suggesting high abundances of presolar diamonds and SiC/graphite, respectively. The cosmic-ray exposure age cannot be determined precisely, because the shielding depth of our Tagish Lake samples is unknown, but the minimum exposure age was determined to be 5.5+/-0.7 Myr on the basis of cosmogenic 21Ne concentrations and the highest 21Ne production rate. X-ray and electron-microscopic study showed that the carbonate-rich lithology is dominated by loosely packed porous matrix that consists mainly of fine-grained saponite and ferromagenesian carbonate. The matrix contains very few chondrules, but many fine-grained clasts having angular shape with longest dimensions up to 1 mm. The clasts differ from host matrix in both texture and mineralogy. They are massive, compacted material with porosity much lower than matrix and contain abundant magnetite and a coherent intergrowth of serpentine and saponite that is rare in matrix. The presence of texturally and mineralogically distinct clasts indicates that the carbonate-rich lithology is a breccia, but the absence of solar noble gases and impact-induced deformational features in host matrix distinguish it from an asteroid regolith breccia. Our results instead indicate that it is an accretionary breccia formed by simultaneous accretion of diverse objects in a massive dust cloud. The clasts often enclose chondrules and anhydrous silicate fragments such as low-iron-manganese-enriched olivines. This observation and their highly compacted, angular morphology suggests that the clasts derive from earlier-formed chondritic materials which have experienced compression and fragmentation due to mild impacts and from which they were excavated and incorporated into the final rock. It is thus suggested that, in the course of planetesimal formation, agglomeration and disagglomeration of small parent bodies occurred repeatedly in a dense dust cloud where solar wind from the infant sun was shielded. The fine-grained ferromagnesian carbonates must have precipitated from aqueous solutions after the assembly of the Tagish Lake asteroid from recycled materials from previous bodies, because the carbonates coat the surfaces of pores and fill in veins in the clasts.
Keywords: TAGISH LAKE; ACCRETIONARY BRECCIA; NOBLE GASES; MINERALOGY; CARBONATE-RICH LITHOLOGY